Erratum: Origin and structure of polar domains in doped molecular crystals - E. Meirzadeh (Nature Portfolio, 2017)
Nature Communications 7: Article number: 13351 (2016); Published: 8 November 2016; Updated: 9 May 2017 In Fig. 1 of this Article, the top crystallographic face of the crystal was inadvertently mislabelled ‘(0͞10)’ during the production process. It should read ‘(010)’. The correct version of Fig. 1 appears below.